Anti-diabetic potential of Catharanthus roseus Linn. and its effect on the glucose transport gene (GLUT-2 and GLUT-4) in streptozotocin induced diabetic wistar rats - Al-Shaqha, Waleed M. (BMC Complement Altern Med, 2015)
BACKGROUND: Catharanthus roseus is an important Ayurvedic medication in traditional medicine. It is potentially used in countries like India, South Africa, China and Malaysia for the healing of diabetes mellitus. Although, the molecular mechanisms behind this effect are yet to be exclusively explored. Due to the great antidiabetic and hyperlipidemic potential of c. roseus, we hypothesized that the insulin mimetic effect of ethanolic extract of c. roseus might add to glucose uptake through improvement in the expression of genes of the glucose transporter (GLUT) family messenger RNA (mRNA) in liver. METHODS: STZ-induced diabetic rats treated by ethanolic extract of c. roseus 100 mg/kg and 200 mg/kg; and one group treated with Metformin (100 mg/kg). After final administration of treatment of 4 weeks, blood samples were collected under fasting conditions, and the body weights (BWs) were measured. Total RNA from liver was extracted with the Qiagen RNEasy Micro kit (GERMANY) as described in the manufacturer’s instructions. First-strand complementary DNA (cDNA) was synthesized at 40 °C by priming with oligo-dT12–18 (Invitrogen, USA) and using Super ScriptII reverse transcriptase according to the protocol provided by the manufacturer (Invitrogen, USA). Real-time polymerase chain reaction (PCR) amplifications for GLUT-4 (gene ID: 25139) were conducted using Light-Cycler 480 (Roche, USA) with the SyBr® I nucleic acid stain (Invitrogen, USA) according to the manufacturer's instructions. Polymerase chain reaction products of β-actin primer gene were used as an internal standard. RESULTS: The proposed study was framed to look at the antidiabetic efficacy of ethanolic extract of c. roseus and an expression of GLUT-2 and GLUT-4 gene in streptozotocin induced diabetic wistar rats. The doses were administered orally at a rate of 100 and 200 mg/kg and detrain the glucose transport system in liver for 4 weeks. The observed results showed a good positive correlation between intracellular calcium and insulin release levels in isolated islets of Langerhans. The supplementation of ethanolic extract of c. roseus significantly amplified the expression of GLUT gene mRNA by Real Time PCR in liver of diabetic rats. CONCLUSIONS: We conclude that the observed antidiabetic effect of c. roseus on STZ induced diabetes was a result of complex mechanisms of GLUT gene mRNA expression. The findings are very encouraging and greatly advocate its candidature for the design of a novel herbal drug to cure deadly diabetes.